RESISTENSI TERHADAP METHICILLIN (METHICILLIN RESISTANT) STAPHYLOCOCCUS AUREUS DI INSTALASI RAWAT INAP - Wildana .; Nurhayana Sennang; Benny Rusli (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2010)
Methicillin Resistant Staphylococcus aureus (MRSA) is a major nosocomial pathogen worldwide. MRSA infection typically aggravatesthe patient condition. MRSA infection increases morbidity and mortality. The study was aimed to find out the MRSA occurrence inDr. Wahidin Sudirohusodo Hospital Makassar patients during July 2008–June 2009. A retrospective study was performed using datafrom the medical records including the results of culture and antimicrobial susceptibility test in Dr. Wahidin Sudirohusodo HospitalMakassar. Among 1082 results of the culture test, 5.2% were identified as Staphylococcus aureus, consist of 51.8% MSSA (MethicillinSensitive Staphylococcus aureus) and 48.2% MRSA. Most of the MRSA patients were treated in orthopaedic surgery (30%), internal(22%), and paediatric (19%) wards. Based on the clinical conditions, most of the patients were in post surgery care (44.4%), pneumonia(18.5%), and diabetic foot (7.5%). All of the MRSA isolates were multiresistant (resistant to three or more antimicrobials) but 96%remain sensitive to vancomycin. It was concluded that most of MRSA patients were staying in the orthopaedic surgery ward. Based onthis clinical condition, most of the patients were in the post surgery care. All of the MRSA isolates were multiresistant, but most of themremain sensitive to vancomycin.